The positive effect of perceived social support and moral resilience between moral injury and health-related productivity loss among emergency nurses - Sun, Xiaoting; Wang, Bingjie; Zhu, Meiyu; Wu, Daiying; Yang, Miaomiao; Zhang, Chunmei (Frontiers in Public Health, 2025)
BackgroundEmergency nurses frequently experience moral injury (MI) arising from high-risk ethical conflicts, heavy workloads, and exposure to traumatic events, which can contribute to health-related productivity loss (HRPL). However, the underlying mechanisms remain unclear. Crucially, perceived social support and moral resilience may mediate this relationship by mitigating negative effects. Clarifying the mediating roles of perceived social support and moral resilience is essential to evaluate their influence on the relationship between MI and productivity loss, and to establish a model that explains this mechanism, thereby contributing to protecting nurses’ well-being and safeguarding patient care quality.ObjectiveThis study aims to explore the relationship between MI and HRPL, and to examine the mediating roles of social support and moral resilience. These insights are of great significance for enhancing the physical and mental well-being of emergency nurses and improving the overall quality of medical care.MethodsA prospective cross-sectional survey was conducted among 483 emergency nurses from five tertiary hospitals across three provinces in mainland China between January and May 2025. The survey instruments included the General demographic questionnaire, Moral Injury Symptoms Scale-Health Professionals Version (MISS-HP), Rushton Moral Resilience Scale (RMRS), Perceived Social Support Scale (PSSS) and Stanford presenteeism scale-6 (SPS-6). Descriptive analysis and Pearson correlation analysis were performed using SPSS 29.0. The structural equation model was constructed with AMOS 29.0 software, and Bootstrap testing was conducted.ResultsThe results showed that moral injury directly affected Health-related productivity loss (β = 0.282, 95% CI [0.183, 0.382]). Perceived social support and moral resilience both played mediating roles in the relationship between MI and HRPL (β = 0.042, 95%CI [0.008, 0.076]) (β = 0.079, 95%CI [0.046, 0.117]). Perceived social support and moral resilience play chain mediating roles between MI and HRPL (β = 0.020, 95%CI [0.010, 0.034]). The structural model demonstrated good fit indices (CFI = 0.947, RMSEA = 0.045), indicating the robustness of the proposed model.ConclusionPerceived social support and moral resilience jointly buffer the impact of MI on nurses’ health-related productivity. Interventions should therefore strengthen both support and resilience. For example, hospitals could implement peer-support groups or resilience workshops, and nurses could practice mindfulness or seek mentorship to bolster coping skills. These strategies may mitigate the negative effects of moral injury and improve productivity. However, as a cross-sectional survey relying on self-reported measures, this study may be subject to response bias, highlighting the need for future longitudinal research.